Guía de Patrimonio Cultural Inmaterial Enfocados a Cuentos, Leyendas y Juegos Tradicionales de la Parroquia Tanicuhí - Cantón Latacunga - Palma Caiza, Alexandra Cristina (2019)
The research project that was carried out in the Tanicuchí Parish was designed to collect information about current intangible cultural manifestations and others that live in the memory of older adults, according to the classification of the National Institute of Cultural Heritage (INPC) is made up of Scopes and sub-scopes, being the case, this research was focused on stories, legends and traditional games, which is found in area 1: Traditions and oral expressions and area 2: Performing Arts. For which techniques and methods were applied that allowed knowing the way of life, customs, and real manifestations that over time have been engraved in the memory of the town to be transmitted from generation to generation. For the development of the project, a situational diagnosis was first carried out in the areas of Socio-cultural, environmental and economic, where the primary and secondary information was collected, in this way the changes that have occurred in each generation were known, both in the way of life as in the number of manifestations: stories, legends and traditional games. In the second stage of the investigation, all the information obtained by classifying the manifestations of area 1 and area 2 was analyzed, an inventory of the cultural manifestations referring to intangible cultural heritage was obtained, the investigation identified key actors ranging from 81 to 100 years old of age, who are the main bearers of the Parish's own identity, 11 manifestations corresponding to area 1 and 22 manifestations of area 2 described above were identified, giving a total of 33 records, this also allowed identifying problems regarding the loss of Cultural identity, due to acculturation and globalization, in this research were described: Tales, legends and traditional games that were captured in a descriptive guide that will allow us to know oral expressions through the dissemination and transmission of manifestations that are part of the identity of the Tanicuchí Parish and have a par point tida for future revitalization projects